Evaluating hydraulic and mechanical properties of weathered intrusive and chemical sedimentary bedrock in South Africa - Dippenaar, Matthys Alois (University of Pretoria, 2025)
Thesis (PhD (Engineering Geology))--University of Pretoria, 2024.